183k views
0 votes
Simplify the expression.

(-1)^5^2/(-2)^-3^2
A) 64
B) 2^-30
C) 2^30
D) 1/64

User Terma
by
5.2k points

1 Answer

4 votes

Answer:

Option A is correct.

A) 64

Explanation:

Given:

The given expression =
((-1^5)^2)/((-2^(-3))^2)

Now we need to simplify the given expression.

Solution:

=
((-1^5)^2)/((-2^(-3))^2)

Rewrite the expression as.

=
(((-1)^5)/((-2)^(-3)))^(2)-------(1)

First we expand numerator
(-1)^(5)=(-1* -1)* (-1* -1)* -1


=(1)* (1)* -1


=(1* 1)* -1


=1* -1


(-1)^(5)= -1

Similarly we simplify the denominator
(-2)^(-3).


(-2)^(-3)=(1)/((-2)^(3))


(-2)^(-3)=(1)/((-2* -2)* -2)


(-2)^(-3)=(1)/(4* -2)


(-2)^(-3)=(1)/(-8)

Now we substitute
(-1)^(5)=-1 and
(-2)^(-3)=(1)/(-8) in equation 1.


(((-1)^5)/((-2)^(-3)))^(2)=((-1)/((1)/(-8)))^(2)

Negative sign is cancelled.


(((-1)^5)/((-2)^(-3)))^(2)=((1)/((1)/(8)))^(2)

So we write the equation as.


(((-1)^5)/((-2)^(-3)))^(2)=8^(2)


(((-1)^5)/((-2)^(-3)))^(2)= 64

Therefore the answer is 64

User Trevor Norris
by
4.8k points